A new approach for solving nonlinear singular boundary value problems - Zhu, Hui; Niu, Jing; Zhang, Ruimin; Lin, Yingzhen (Mathematical Modelling and Analysis, 2018)
In this paper, an e_cient method based on Quasi-Newton's method and the simpli_ed reproducing kernel method is proposed for solving nonlinear singular boundary value problems. For the Quasi-Newton's method the convergence order is studied. The uniform convergence of the numerical solution as well as its derivatives are also proved. Numerical examples are given to demonstrate the e_ciency and stability of the proposed method. The numerical results are compared with exact solutions and the outcomes of other existing numerical methods.